Ashabul A’raf dan Konsep Manzilah bayn al-Manzilatain: Studi Komperatif Tafsir al-Kasysyaf dan Tafsir Ibnu Katsir - Ningsih, Fitria (Maliki Interdisciplinary Journal, 2023)
The Qur’an teaches that there is another better life after the life in this world called the Hereafter. It is in this afterlife that all beings account for their deeds while in this life. If his good deeds are more then he will be in heaven, while if his bad deeds are more, he will be in hell. In the Qur’an, there is also a verse that describes a place called Al-A’raf, a place that exists between heaven and hell. Regarding this, the mufassir scholars have different opinions as to who and how the fate of the occupants of Al-A’raf. One of the famous mufassir from among the Mu’tazilites, al-Zamakhshari in al-Kasysyaf interprets that the inhabitants of Al-A’raf are Believers who commit great sins. He did not go to heaven because of his sin and did not go to hell because of his faith. This interpretation was strongly influenced by the Mu’tazilite teachings known as manzilah baina al-Manzilatain. Another mufassir who is no less famous, namely Ibn Kathir in Tafsir Ibn Kathir interprets that the inhabitants of Al-A’raf are people whose good and bad deeds are balanced. They waited on high (Al-A’raf) until Allah decreed them to go to heaven. Because of that difference, the author wants to examine the differences in the interpretation of these two mufassir through methods, interpretive approaches, and the scientific background of the mufassir.